Ethnicity and Development in Africa: A Reappraisal - Bates, Robert H (American Economic Review, 2000)
131 enroll. While membership is an entitlement that can be activated, the entitlement is restricted by family membership. As in other developing regions, formal institutions are weak in modern Africa, and persons therefore tend to organize economic relationships through social institutions. One way of augmenting the stock of capital is through education; another is through migration to the city. To a great degree, it is families who organize the flow of resources that promote both urban migration and the acquisition of skills. Recognizing the central role of families in the formation of capital, one can achieve a better grasp of the relationship between modernization and ethnicity. To a significant degree, modernization is achieved through the process of human-capital formation. This process is privately organized; that is to say, it is organized by families. Families organize the flow of resources between generations and sectors, thus promoting the acquisition of skills and urban migration, and thus the modernization of societies. It is by stabilizing the contract between generations within family units that ethnic groups facilitate the process of investment. To illustrate, I use data collected from a village in Luapula Province, Zambia, which supplies labor to the mining centers of Zambia and Congo. When conducting my field work, I focused on links between town and country and found that the income rural dwellers derived from town varied systematically with the structure (size, age composition, and education) of their families. The coefficients in the “remittance” function suggested that an additional child yields, on average, 3.23 kwacha in the form of financial Those who study modern Africa commonly highlight three features: its poverty, its instability, and its ethnic diversity. Whether in lurid popularizations (e.g., Robert Kaplan, 1994) or in social scientific research (e.g., William Easterly and Ross Levine, 1997; but see also Paul Collier and A. Hoeffler [1998]) scholars reason that Africa is poor because it is unstable and that its instability derives from its ethnic complexity. Ethnicity thus lies, it is held, at the root of Africa’s development crisis. This essay critiques the conventional wisdom by mounting an alternative interpretation. Using both qualitative and quantitative data from Africa, this article argues that: